Vendor managed inventory via SOA in healthcare supply chain management - (:unkn) unknown (My University, 2012)
As the management of supply chain gains an important role for the companies in order to be competitive in the market, healthcare sector also has effected from this wave. The main difference between the healthcare supply chain management and the other sectors are the key elements. In healthcare sector, pioneers must do highly accurate job because, in this sector, cost of an error may be someone's life. In healthcare sector, "Right product must be in the right place at the right time" is really a must. This paper shows a new modelling approach of healthcare supply chain in order to ensure this mandatory accuracy by using vendor managed inventory (VMI) technique. The core theme of this paper is that, to provide the best kind of process systems by using service oriented architecture patterns to model vendor managed inventory in order to ensure an effective management in healthcare supply chain management. Copyright © 2012 Inderscience Enterprises Ltd.
Keywords: Continuous replenishment; Healthcare supply chain management; Service oriented architecture; SOA; Vendor managed inventory; VMI; Web services modelling